From an Atypical Wake‐promoting Agent to Potent Histamine‐3 Receptor Inverse Agonists. (13th February 2013) - Dunn, Derek; Raddatz, Rita; Ator, Mark A.; Bacon, Edward R.; Chatterjee, Sankar
<x xml:space="preserve">Abstract</x> Utilizing atypical wake‐promoting agent modafinil (inactive in both rH3 and hH3 binding assays) as a launching pad, a series of sulfinyl‐ and sulfone‐derived H3 receptor inverse agonists were developed. Brain‐permeable compound 27, a potent member of the series displayed excellent selectivity against related family members (H1, H2, and H4 receptors).